Strength Behavior of Flat and Folded Fly Ash-Based Geopolymer Ferrocement Panels under Flexure and Impact - Dharmar Sakkarai; Nagan Soundarapandian (Advances in Civil Engineering)
This paper presents the impact of fiber and wire mesh layers on the strength behavior of flat as well as folded fly ash-based geopolymer ferrocement panels. The behaviors, namely, flexural strength, impact strength, ductility, stiffness, and cracking patterns, are observed. With the objective of decreasing CO2 emissions, concrete utilizes wastes such as fly ash disposed by industrial sectors. Six panels (three flat and three folded) were cast utilizing a fly ash-dependent geopolymer mortar of size 1000 mm × 400 mm × 30 mm in addition to two panels of each type for the impact study. Heat curing in a temperature-controlled chamber maintaining 75°C to 80°C for 24 hours was done after 24 hours of the resting period. The experimental results indicated that the flexural strength got enhanced by 33 percent by increasing the quantity of wire mesh layers, but the ductility got decreased by 30 percent for the flat panels; however, there was no noticeable impact in the case of folded panels. The flexural strength of the folded panel was found to be three times greater than that of the flat panels. In addition, it is noticed that the behavior of the fiber-reinforced flat as well as folded panels of single layer mesh is stronger than the double layer wire mesh panels regarding cracking and ultimate load. Furthermore, the impact strength of the folded panels was found to be 90% greater than that of flat panels, and the energy absorbed at failure was directly proportional to the volume of reinforcement provided in the panels. Moreover, the failure pattern of the impact tested specimens showed punching shear as the predominant factor.